A new species of Bunium (Apiaceae: Apioideae) from Central Anatolia in Turkey: Bunium sivasicum - Çeli̇k Mustafa; Bağci, Yavuz (Phytotaxa, 2019)
A new species of Bunium from Central Anatolia (Turkey), Bunium sivasicum (Apiaceae), is described and illustrated. The taxonomic affinities of the new species are determined by detailed morphological investigation and molecular phylogenetic study. Nuclear rDNA-ITS region sequences are used to reveal the phylogenetic relationship of the new species. It belongs to the sect. Elegantia and is related to Bunium simplex, B elegans and B. verruculosum. The differences between the new species and its allies are discussed. Pollen characteristics and fruit surface features of the new species are investigated. The anatomical structure of the fruit is given in detail. In addition, the geographical distributions of the Bunium sivasicum and related taxa in Anatolia are also mapped.